Pengaruh Proporsi Biji Kurma Dan Tepung Beras Terhadap Sifat Fisik Masker Wajah - Heyda Putri Nastiti; Dindy Sinta Megasari; Nia Kusstianti; Sri Dwiyanti (Jurnal Tata Rias, 2025)
Facial care can be performed both internally and externally. One external treatment method involves using natural face masks, such as those made from date seeds and rice flour. This research aims to analyze (1) the effects of the proportion of date seeds and rice flour on the physical characteristics of face masks, including color, odor, texture, adhesion, and viscosity, and (2) the optimal storage duration of the face masks. The study employs a pre-experimental method with the independent variable being the proportion of date seeds and rice flour, while the dependent variables include the physical characteristics and storage duration. Data were collected through observations made by 30 panelists and microbiological testing. Data analysis was conducted using one-way ANOVA and Duncan's test with SPSS version 29. The findings indicate that the ingredient proportions significantly affect the physical characteristics of the masks in samples X1, X2, and X3. The mask with a 2:1 proportion (X2) had the highest average score (3.19) and a storage duration of up to the 5th week, with a total microbial count of 3.1 × 10² CFU/ml, which remains below the standard limit of unsuitability for use. In conclusion, the face mask with the X2 proportion provides the best results in terms of physical characteristics and storage duration. Keywords: facial mask, date seed, rice flour, shelf life.